Studi Literatur: Creative Problem Solving terhadap kemampuan berpikir kreatif dan pemecahan masalah matematis siswa - Laili Octadianti; Flavia Aurelia Hidajat; Meiliasari Meiliasari; Lukman El Hakim (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2023)
This study aims to investigate the lack of students' creative thinking and problem solving skills in learning mathematics. Mathematics is a structured and systematic science, as a human activity through an active, dynamic, and generative process, and as a science that develops critical, objective, and open thinking attitudes. This research is a literature study with a descriptive qualitative research type with a literature review that seeks to describe Creative Problem Solving on students' creative thinking and mathematical problem solving skills. The purpose of this research is to review the literature on Creative Problem Solving on students' creative thinking and mathematical problem solving skills. Data collection is done by collecting various written sources, such as articles, journals, and documents relevant to the study in this research to be read and reviewed. After the data is collected, testing and comparing the data found is carried out. Data analysis techniques were carried out qualitatively with content analysis and quotation of appropriate opinions. The study results show that Creative Problem Solving is one of the learning models that can develop aspects of creative thinking and problem solving skills. The learning model is designed as a variation of problem solving learning with a systematic technique in organizing creative ideas to solve problems. Based on this, to develop creative thinking and problem solving skills is to apply the Creative Problem Solving learning model which contains a process, method, or system to approach problems in an imaginative way and produce effective actions.